Early Childhood Sex Education Media as a Preventive Step for Sexual Violence - Dahlia, Dahlia; Sutrisno, Sutrisno; Qibtiyah, Alimatul (Jurnal Ilmiah Peuradeun, 2021)
This study aimed to overcome problems related to the lack of integrated sex education media in integrated thematic learning so that it can make it easier for teachers to deliver sex education materials to early childhood. This research is a type of research and development. This study employed the Borg and Gall development model which consists of two main objectives, namely developing products and validating the resulting products. The population in this study was Jogja Green School and Aisyiyah Pembina Piyungan Kindergarten. The research sample chosen in Jogja Green School was 13 children and in Aisyiyah Pembina Piyungan Kindergarten as many as 30 children. The questionnaire as an instrument was used to validate and evaluate the quality of the developed product. The data analysis technique applied was descriptive qualitative analysis and descriptive statistics. The results of the study showed that: (1) The results of the validation of material experts, media experts, and education practitioners on the products developed were feasible to use, (2) The results of the limited trial showed that the product developed was suitable for use, (3) The results of the trial were more widely known that the product developed was suitable to use and was effective in increasing knowledge of early childhood sex education.